1996
DOI: 10.1074/jbc.271.7.3336
|View full text |Cite
|
Sign up to set email alerts
|

Receptor and Membrane Interaction Sites on Gβ

Abstract: The functional organization of Gbetagamma is poorly understood. Regions of bovine brain Gbetagamma that interact with a photoaffinity derivative of an alpha2-adrenergic receptor-derived peptide from the third intracellular loop (diazopyruvoyl-modified peptide Q (DAP-Q)) and a hydrophobic membrane probe (3-trifluoromethyl-3-(m-iodophenyl)diazirine (TID)) were examined. We previously showed that DAP-Q cross-links to specific, competable sites on both the alpha and beta subunits of Go/Gi but not on the gamma subu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
61
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(68 citation statements)
references
References 47 publications
7
61
0
Order By: Relevance
“…These results imply interaction of the fusion protein with the ␤␥ complex, but understanding the details of this will require further study. It is of interest in this regard to note, however, that Taylor et al (36) have previously indicated a role for ␤␥ in receptor stimulation of the GTPase activity of the ␣ 2A -adrenoreceptor.…”
Section: Fig 4 Uk14304 Stimulates High Affinity Gtpase Activity Of mentioning
confidence: 96%
See 1 more Smart Citation
“…These results imply interaction of the fusion protein with the ␤␥ complex, but understanding the details of this will require further study. It is of interest in this regard to note, however, that Taylor et al (36) have previously indicated a role for ␤␥ in receptor stimulation of the GTPase activity of the ␣ 2A -adrenoreceptor.…”
Section: Fig 4 Uk14304 Stimulates High Affinity Gtpase Activity Of mentioning
confidence: 96%
“…Given the nature of the physical linkage between the receptor and G protein in the fusion proteins, the knowledge that the N terminus of the G protein ␣ subunit plays a central role in interaction with the ␤␥ complex (28 -29), the concept that the ␤␥ complex may play a key role in receptor interactions with the ␣ subunit (33)(34)(35), and the understanding that G protein ␣ subunit acylation is important in interactions with the ␤␥ complex, it was of considerable interest to observe that coexpression of excess ␤ 1 ␥ 2 along with any of the ␣ 2A -adrenoreceptor-G i1 ␣ fusion proteins resulted in greater maximal UK14304 stimulation of GTPase activity (Fig. 5).…”
Section: Fig 4 Uk14304 Stimulates High Affinity Gtpase Activity Of mentioning
confidence: 99%
“…This portion together with the flexible part could serve as a counterpart to the bipartite receptor recognition site on the G protein. specifically be cross-linked to both the ct-and fl-subunits of the corresponding G protein [31]. Mastoparan, on the contrary, can form only cross-links to the ~subunit [32], indicating that mastoparan is able to fulfill only one aspect of the structural requirements for G protein coupling.…”
Section: Discussionmentioning
confidence: 99%
“…For the rat vasopressin V 1a receptor, a peptide mimicking its second intracellular loop was found to specifically inhibit vasopressin-specific binding (2). In other cases, short peptides mimicking GPCR third intracellular loops were found to act on the coupling between the receptor and the G protein (3)(4)(5)(6)(7)(8). Expressed as a minigene, the ␣ 1b -adrenergic i3 loop was shown to inhibit Gq signaling (9).…”
mentioning
confidence: 99%